Aesthetic Management of an Unerupted Maxillary Central Incisor with a Closed Eruption Surgical Technique: A Case Report (Medicine Today, 2023)
Introduction: Treatment of impacted teeth requires a combination of orthodontics and surgery.Case report: Reported case is of a 12-year-old-girl with an unerupted maxillary central incisor obstructed by an odomtome.Discussion: Surgical exposure was done and traction with closed eruption technique was used.Result: The tooth was aligned in the dental arch with accepted aesthetic and functional satisfaction of the patient.Medicine Today 2023 Vol.35(2): 134-136